Quarantine treatment against mediterranean fruit fly (Ceratitis capitata Wiedemann) in mangoes haden variety (Mangifera indica) with gamma irradiation (Co 60) - Peña C., María E. (2010)
Tephritidae fruit flies are among the most damaging pests of fruit crops worldwide Ceratitis capitata Wiedemann, for instance, can infest more than 250 fruit and vegetable crop species, and constitutes the main phytosanitary restrict for export purposes. The investigation was carried out in a SENASA’s Production Center of Sterile Fruit Flies and PIMU’s laboratory; it was supervised by an OIEA’s irradiation expert. This research comprised two stages: 1) Determine the minimum irradiation dose to avoid emergence of fruit fly adults (bioassay test), and 2) Evaluate 30 000 individuals having been exposed to the minimum effective dose to provide statistically reliable data (confirmatory test). It was confirmed that no adult emergence occurred at 0,1 kGy, and no significant differences were found between treated and non-treated mangoes when both chemical and organoleptic tests were applied.